Efek Samping Hipoglikemi yang Dialami oleh Pasien Geriatri yang Berisiko Sindrom Metabolik: Side Effects of Hypoglycemic Experienced by Geriatric Patients Who are at Risk of Metabolic Syndrome - Ditya Ayu Natalia; Sugiyarto Sugiyarto; Endang Darmawan (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Metabolic syndrome is a collection of symptoms of metabolic problem of the body with a several diseases. This study was to observe the relationship of geriatric patients characteristics versus clinical conditions (blood pressure, blood glucose, cholesterol and triglyceride) and find out which drugs are most often used. This research was conducted in 3 hospitals in Yogyakarta retrospectively. The number of respondents to the study was 101 geriatric patients who were at risk of metabolic syndrome and experienced hypoglycemic side effects. The data was collected using medical record data. Data analysis of the characteristics of respondents and drug groups was carried out descriptively. The relationship of the subject characteristics and the clinical state of the patient was carried out by using Chi-square. The results saw that the majority of geriatric patients who are at risk of developing metabolic syndrome are women (52.38%) with a normal body mass index (71.43%). More common history of diseases experienced by geriatric patients at risk of metabolic syndrome are diabetes mellitus and hypertension (60,95%) and patients with no complications (67.62%). The history of the disease correlates with the clinical state of the patient in particular cholesterol and triglyceride levels (p<0,05). In addition, complications correlate also with blood pressure values (p<0,05). The most commonly used classes of drugs in geriatric patients at risk of metabolic syndrome are ARB antihypertensive (76.19%), insulin antidiabetics (50,48%), and statin antidislipidemia (41.90%).